Therapy for memory and attention impairments in young patients - Elena Glebovna Filatova; M V Naprienko (Неврология, нейропсихиатрия, психосоматика, 2013)
Objective. To study the efficacy and tolerance of tanakan in the treatment of mild cognitive impairment in young patients. Patients and methods. The study enrolled 30 patients whose mean age was 33.5±7.5 years. It used clinical neurological examination; a test for rating general condition, activity, and mood; studies to evaluate aural short-term and verbal short-term memories and to estimate the level of attention using Schulte's tables, and questionnaires for the rating of autonomic disorders and nocturnal sleep quality, those for the patient subjective assessment of treatment efficiency and for the recording of adverse reactions. Results. Tanakan therapy led to the normalized emotional status in the patients, improved nocturnal sleep, and reduced autonomic disorders. There was a tendency towards improvement of all characteristics of attention. Aural and verbal memories became better. Conclusion. Tanakan is an effective and safe drug to treat cognitive impairment at any age.